Omics Biomarkers in Obesity: Novel Etiological Insights and Targets for Precision Prevention - Aleksandrova, Krasimira (Curr Obes Rep, 2020)
PURPOSE OF REVIEW: Omics-based technologies were suggested to provide an advanced understanding of obesity etiology and its metabolic consequences. This review highlights the recent developments in “omics”-based research aimed to identify obesity-related biomarkers. RECENT FINDINGS: Recent advances in obesity and metabolism research increasingly rely on new technologies to identify mechanisms in the development of obesity using various “omics” platforms. Genetic and epigenetic biomarkers that translate into changes in transcriptome, proteome, and metabolome could serve as targets for obesity prevention. Despite a number of promising candidate biomarkers, there is an increased demand for larger prospective cohort studies to validate findings and determine biomarker reproducibility before they can find applications in primary care and public health. SUMMARY: “Omics” biomarkers have advanced our knowledge on the etiology of obesity and its links with chronic diseases. They bring substantial promise in identifying effective public health strategies that pave the way towards patient stratification and precision prevention.